Do admission glucose levels aid in predicting mortality associated with community-acquired pneumonia?. Issue 4 (19th October 2017) - Postma, Douwe F.; van Werkhoven, Cornelis H.; Troeman, Darren P.R.; Sankatsing, Sanjay U.C.; Oosterheert, Jan Jelrik; Bonten, Marc J.M.
Diabetes mellitus increases the risk of and mortality associated with community-acquired pneumonia (CAP) [1]. Hyperglycaemia negatively impacts both the innate and adaptive immune response, which could lead to decreased bacterial clearance and increased mortality from infection [2]. This can be extended to non-diabetic patients as well: hyperglycaemia on admission is an independent risk factor for higher complication rates, longer length of stay, and higher mortality in diabetics and non-diabetics with CAP [3–6]. Hypoglycaemia on admission has also been associated with an independent increased risk of mortality in patients with CAP [7, 8]. Currently, two severity scoring systems are widely used for predicting CAP mortality: the pneumonia severity index (PSI) and CURB-65 score (confusion, urea >7 mmol·L −1, respiratory rate ≥30 breaths·min −1, blood pressure <90 mmHg (systolic) or ≤60 mmHg (diastolic), age ≥65 years) [5, 9]. Admission glucose levels (AGL) are part of the PSI, as a categorical variable for hyperglycaemia, but not of CURB-65. We, therefore, investigated whether AGL contributes to these severity scores when both hypo- and hyperglycaemic states are appropriately modelled. Admission glucose levels do not improve discrimination of current severity scores in community-acquired pneumonia http://ow.ly/Dyrz30f7Bwi